Unleashed - McCulloch, Amy, 1986- (McCulloch, Amy, 1986- Jinxed, 2021)
Armed with their companioneering and coding skills and accompanied by their loyal bakus, Lacey Chu and her friends attempt a rescue mission deep in the heart of a sinister transnational tech corporation.